2012
DOI: 10.1021/la3015157
|View full text |Cite
|
Sign up to set email alerts
|

Reactions and Surface Interactions of Saccharides in Cement Slurries

Abstract: Glucose, maltodextrin, and sucrose exhibit significant differences in their alkaline reaction properties and interactions in aluminate/silicate cement slurries that result in diverse hydration behaviors of cements. Using 1D solutionand solid-state 13 C nuclear magnetic resonance (NMR), the structures of these closely related saccharides are identified in aqueous cement slurry solutions and as adsorbed on inorganic oxide cement surfaces during the early stages of hydration. Solid-state 1D 29 Si and 2D 27 Al{ 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 64 publications
5
33
0
Order By: Relevance
“…47 It was also reported that saccharides affect hydration of cements depending on the reaction and adsorption behavior of saccharides and their degradation products with dissolved species and particle surfaces. 48,49 Similar to the retardation effect of saccharides on aluminate hydration, we observed a decrease in bound water content in the presence of low molecular weight saccharides. 36,38,39 As mentioned earlier, the addition of NaCl did not affect the bound water, while the H + and OH − led to a decrease and increase of the bound water peaks, respectively.…”
Section: Bound Water Layersupporting
confidence: 74%
“…47 It was also reported that saccharides affect hydration of cements depending on the reaction and adsorption behavior of saccharides and their degradation products with dissolved species and particle surfaces. 48,49 Similar to the retardation effect of saccharides on aluminate hydration, we observed a decrease in bound water content in the presence of low molecular weight saccharides. 36,38,39 As mentioned earlier, the addition of NaCl did not affect the bound water, while the H + and OH − led to a decrease and increase of the bound water peaks, respectively.…”
Section: Bound Water Layersupporting
confidence: 74%
“…Vicat needle penetration depth in FRA pastes prepared with different saccharose concentrations. retarder effect [58,59]. This delay increases with increasing saccharose concentration (it is particularly significant above 2%), which suggests a potential chemical reaction.…”
Section: Time (H)mentioning
confidence: 91%
“…12,14,21,23−27 Solid-state 2D 13 C{ 1 H}, 29 Si{ 1 H}, and 27 Al{ 1 H} heteronuclear correlation (HETCOR) and 1 H{ 1 H} double-quantum (DQ) NMR measurements of silicates and aluminates hydrated with organic additives (e.g., stabilizers or hydration inhibitors) have established surprisingly diverse influences of closely related organic molecules, such as glucose and sucrose, on the rates of hydration. 13,28,29 Similar 2D NMR methods have also been used to measure the molecular interactions of organic acids adsorbed at much higher concentrations (4−40% bwos) on titania and zirconia nanoparticles that also have high surface areas (50−150 m 2 /g). 30 As conventionally practiced, however, NMR spectroscopy is relatively insensitive, so detecting and resolving the NMR signals from organic molecules and inorganic species in low-surface-area cementitious materials have required concentrations of at least 1% bwos of the organic species, which furthermore must often be isotopically enriched to be feasible.…”
Section: ■ Introductionmentioning
confidence: 99%